2011
DOI: 10.1002/ibd.21631
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin generation in pediatric patients with Crohnʼs disease

Abstract: Our study clearly shows that the active state of CD in children is associated with the potential for high thrombin generation, but this seems to be caused mainly by the inflammatory process and not by a preexisting propensity for high thrombin generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
20
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 20 publications
9
20
0
1
Order By: Relevance
“…PLT plays a vital role in the physiology of primary hemostasis and in the pathophysiological activity of arterial thrombosis. Over the past decades it has been demonstrated that PLT also plays a crucial role in the pathophysiology of inflammation, especially invascular inflammation . PLT interacts with leukocytes, small muscle cells (SMCs) and endothelial cells, and secretes a large amount of cytokines and chemokines, thereby, initiates and propagates the inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PLT plays a vital role in the physiology of primary hemostasis and in the pathophysiological activity of arterial thrombosis. Over the past decades it has been demonstrated that PLT also plays a crucial role in the pathophysiology of inflammation, especially invascular inflammation . PLT interacts with leukocytes, small muscle cells (SMCs) and endothelial cells, and secretes a large amount of cytokines and chemokines, thereby, initiates and propagates the inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity and specificity of these parameters are not quite satisfactory, especially in patients with relatively low high‐sensitivity CRP (hs‐CRP) levels, while the disease may be remarkably active as verified by the Crohn's disease activity index (CDAI) and endoscopy. There is emerging evidence that platelet (PLT) may play a role in the pathogenesis of CD . PLT value can be obtained from the routine complete blood count, which is less invasive with a lower cost compared with the abovementioned methods.…”
Section: Introductionmentioning
confidence: 99%
“…10 In addition, the role of thrombin generation extends far beyond the sole coagulation system. Several recent findings have emphasized its key impact in atherosclerosis, 11 diabetic nephropathy, 12,13 and inflammatory diseases such as sepsis, 14 Crohn disease, 15 and sickle cell disease. 16 Altogether these observations clearly emphasize the importance of identifying factors controlling the interindividual variability of thrombin generation.…”
Section: Introductionmentioning
confidence: 99%
“…Çocukluk çağı ülseratif kolit hastalığına bağlı beyin ven trombozu / Cerebral venous thrombosis associated with childhood ulcerative colitis artış ve azalmış antitrombin III düzeyi bildirilmektedir (12). Yine aktif hastalık döneminde belirgin olarak artan endojen trombin potansiyeli trombin oluşumunu hızlandırarak doğal antikoagülan yollarda işlev bozukluğuna neden olur ve tromboza eğilimi arttırır (13,14). Tüm bunlara ek olarak tümör nekrozis faktör α üretiminde artış (15), bağırsaktaki glikozaminoglikan üretiminde azalma da prokoagülan etki yapabilir (16).…”
Section: Discussionunclassified